A NUMERICAL STUDY OF THE COMPARISON OF NORMAL CONCRETE AND LIGHT WEIGHT CONCRETE EXTERIOR BEAM-COLUMN JOINTS BEHAVIOR TO CYCLIC LATERAL LOADS - Nurjannah, Siti Aisyah; Saloma; Usman, Arie Putra; Wibowo , Muhammad Lindung Persada Putra (Journal of Applied Engineering Science, 2022)
This paper presents a numerical analysis of the exterior Beam-Column Joints (BCJ) in resisting a combination of constant axial and lateral cyclic loads. The materials used in this study were Normal Concrete (NC) and Light Weight Concrete (LWC). Light Weight Concrete has been commonly used to reduce the mass of buildings and minimize the structural damages due to earthquakes. A numerical model of exterior BCJ using NC materials was verified using experimental data from the previous research. Then, these models of exterior BCJ using NC and LWC materials were analyzed to obtain the performance. This study aimed to elaborate on the LWC as materials of structures to resist earthquake loads. The performance of the exterior BCJ models was analyzed through hysteretic curves, ductility, stiffness degradation, and strength degradation. The analysis results showed that the NC-BCJ model achieved a higher maximum story drift of 5.3% than the LWC-BCJ model of 4.5%. NC-BCJ model reached higher maximum lateral forces of 40.58 kN and 40.51 kN under push and pull loads, compared with the LWC-BCJ model of 27.83 kN and 32.40 kN. The exterior NC-BCJ model satisfied the strength criteria in the ACI 374.1-19 with a ratio of 1.0 under push and pull loads. Despite the lower maximum lateral forces achieved by the LWC-BCJ model than NC-BCJ, it satisfied this criterion with ratios of 0.93 and 0.99 under push and pull loads, respectively. Both NC-BCJ and LWC-BCJ models performed moderate ductility of 2.70 and 2.52.
Keywords: lightweight concrete, normal concrete, cyclic lateral load, numerical model, ductility, strength, stiffness